Ventricular assist devices as bridge to heart transplantation: impact on post-transplant infections. Issue 1 (December 2016) - Héquet, Delphine; Kralidis, Georg; Carrel, Thierry; Cusini, Alexia; Garzoni, Christian; Hullin, Roger; Meylan, Pascal; Mohacsi, Paul; Mueller, Nicolas; Ruschitzka, Frank; Tozzi, Piergiorgio; van Delden, Christian; et al.
Abstract Background Ventricular assist devices (VAD) are valuable options for patients with heart failure awaiting cardiac transplantation. We assessed the impact of pre-transplant VAD implantation on the incidence of post-transplant infections in a nationwide cohort of heart transplant recipients. Methods Heart transplant recipients included in the Swiss Transplant Cohort Study between May 2008 and December 2012 were analyzed. Cumulative incidence curves were used to calculate the incidence of bacterial orCandida infections (primary endpoint) and of other infections (secondary endpoint) after transplant. Cox regression models treating death as a competing risk were used to identify risk factors for the development of infection after transplant. Results Overall, 119 patients were included in the study, 35 with a VAD and 84 without VAD. Cumulative incidences of post-transplant bacterial orCandida infections were 37.7 % in VAD patients and 40.4 % in non-VAD patients. In multivariate analysis, the use of cotrimoxazole prophylaxis was the only variable associated with bacterial/Candida infections after transplant (HR 0.29 [95 % CI 0.15-0.57], p < 0.001), but presence of a VAD was not (HR 0.94, [95 % CI 0.38-2.32], p = 0.89, for continuous-flow devices, and HR 0.45 [0.15 – 1.34], p = 0.15, for other devices). Risk for post-transplant viral and all fungal infections was not increased in patients with VAD. One-year survival was 82.9 % (29/35) in the VAD group and 82.1 % (69/84) in the non-VAD group. All 6 patients in the VAD group that died after transplant had a history of pre-transplant VAD infection. Conclusion In this nationwide cohort of heart transplant recipients, the presence of VAD at the time of transplant had no influence on the development of post-transplant infections.